A laboratory study on feeding plasticity of the shredder Sericostoma vittatum Rambur (Sericostomatidae) - Carvalho, Emerson M.; Graca, Manuel A. S. (Springer, 2007)
Since litter input and availability of leaves in many streams is highly seasonal in Portugal, we investigated whether Sericostoma vittatum, a typical shredder, was able to grow using alternative food sources. To test this hypothesis we fed S. vittatum with Alnus glutinosa (alder, CPOM, coarse particulate organic matter), leaf powder from A. glutinosa and Acacia dealbata and FPOM (fine particulate organic matter) from a 5th and a > 6th order river, the macrophyte Myriophyllum aquaticum and biofilm. Growth in S. vittatum was significantly influenced by the food item given (ANOVA, P = 0.0082). The food item promoting the highest growth was A. glutinosa, in the form of FPOM (6.48% day(-1)) and CPOM (4.24% day(-1)); all other forms of FPOM and biofilm provided relatively low growth rates (0.77-1.77% day(-1)). The macrophyte M. aquaticum was also used as food source by S. vittatum and promoted intermediate growth (1.96% day(-1)). Neither nitrogen, phosphorus nor caloric content was correlated with growth. However, since higher growth was achieved with alder, in the form of CPOM and FPOM, we concluded that the chemical content of food was more important for S. vittatum than the physical form of such food. This may partially explain why shredders are able to survive when leaves are scarce in streams.
Keywords: shredder; Sericostomatidae; laboratory study; growth rates; food quality